Application of Meta-SWOT method for tourism development planning of Farsi Island of the Persian Gulf Region - Azita Rajabi; Kamran Jafarpour Ghalehteimouri (Journal of Sustainable Tourism and Entrepreneurship, 2023)
Purpose: Tourism is a pivotal force in contemporary economies, shaping macroeconomic facets, such as national income, financial robustness, and employment opportunities. In an era marked by globalization, nations and urban centers aspire to elevate their competitive stance and augment community well-being through strategic blueprints for the tourism sector. Research Methodology:  This research focuses on the evaluation of Persian Gulf tourism's standing vis-à-vis regional rivals while identifying the tourism assets and competencies of Farsi Island and scrutinizing their Value, Rareness, Imitability, and Organization (VRIO) attributes. The meta-SWOT strategic planning methodology is a paramount tool in this context. Results: The research unfolds in two phases: documentary and bibliographical scrutiny, and comprehensive surveys canvassing insights from ten tourism authorities judiciously chosen through purposive selection. The results shed light on the preeminent sway of macro-level factors, including national macro-management, governmental foreign policy, and international sanctions, as potent determinants of the tourism landscape of Farsi Island. Limitations: This study required long-term secondary analysis of data from Persian Gulf countries. However, these data have only recently been collected in a few countries; therefore, this study is based on primary data collection. Contributions: Concurrently, factors such as inadequate budget allocation and marginalization of the tourism sector within the country play pivotal roles in molding the Persian Gulf region's tourism trajectory.